Time course of bronchoconstrictive response in asthmatic subjects to reduced temperature. - Ramsey, J M (1977)
Thirteen young adults with bronchial asthma and a like number of controls were subjected for 45 minutes to a temperature of 2 degrees C after leaving a temperature of 24 degrees C to which they subsequently returned. Pre-exposure examination included VC, FEV1, MMEF, FEV1/VC%, and urinary catecholamines. The pulmonary measurements were repeated at 15, 80, and 200 minutes after exposure. Catecholamines were measured from a second urine sample, the collection of which corresponded to the period during and after the stress. Controls showed no significant pulmonary changes throughout the time of study, but 15 minutes after exposure the asthmatic subjects showed a significant mean decrease of all pulmonary measurements from pre-exposure values. The controls showed a significant mean increase in urinary catecholamines after the stress, whereas those with asthma showed no significant increase.